Investigation of electronic energy transfer in a BODIPY-decorated calix[4]arene. (December 2019) - Tosi, Irene; Bardi, Brunella; Ambrosetti, Matteo; Domenichini, Edoardo; Iagatti, Alessandro; Baldini, Laura; Cappelli, Chiara; Di Donato, Mariangela; Sansone, Francesco; Sissa, Cristina; Terenziani, Francesca
Abstract: The photophysics of a donor-acceptor system in which efficient electronic energy transfer occurs is analyzed and discussed by the combined use of steady-state and time-resolved spectroscopy and DFT/TD-DFT computations. The donor and acceptor units belong to the class of BODIPY chromophores, and are conveniently linked through a calixarene scaffold, which allows the control of the mutual orientation and distance between chromophores. Our results highlight that the energy transfer process occurs with multiexponential dynamics strongly influenced by the solvent. Although the conformation adopted by the system is very similar in all the analyzed solvents, highly polar media favour fast and efficient energy transfer. On the contrary, in non-polar media, the concomitant occurrence of backward energy transfer causes a significant slowdown of the process. The inverse of the energy transfer rates calculated at the TDDFT level are in very good agreement with the experimental kinetics measured with transient absorption spectroscopy. Graphical abstract: Image 1 Highlights: A BODIPY-decorated calix [4]arene is prepared as model system for energy transfer. Steady-state spectroscopy reveals efficient energy transfer between the BODIPYs. Transient absorption suggest that energy transfer is influenced by medium polarity. Energy transfer rates are calculated at the TD-DFT level of theory.